Durable ventricular assist device implantation for systemic right ventricle: a case series. Issue 6 (18th November 2020) - Tadokoro, Naoki; Fukushima, Satsuki; Hoashi, Takaya; Yajima, Shin; Taguchi, Takura; Shimizu, Hideyuki; Fujita, Tomoyuki
Abstract: Background: A systemic right ventricle (RV) after atrial switch in transposition of the great arteries (TGA) or congenitally corrected TGA (ccTGA) often results in advanced heart failure in adulthood. Case summary: Four patients with INTERMACS Class III underwent durable ventricular assist device (VAD) implantation for a systemic RV. Two patients were diagnosed with ccTGA and underwent tricuspid valve replacement, and two were diagnosed with TGA in childhood and underwent Mustard repair. The two patients with ccTGA received an EVAHEART (Sun Medical, Nagano, Japan) and HeartMate 3 (Abbott Laboratories, Abbott Park, IL, USA) at the age of 56 years and 34 years, respectively. Of the patients with TGA, one received a Heartmate II at age 40 years, and one received a HeartMate 3 at age 40 years. All patients were weaned from cardiopulmonary bypass without subpulmonic VAD support and transferred to the intensive care unit with optimum VAD support. No in-hospital deaths, cerebrovascular accidents, or other major complications occurred. The post-VAD right heart catheter study showed a remarkable reduction in pulmonary capillary wedge pressure in all patients. Discussion: The indications for and surgical technique of durable VAD implantation for a systemic RV after atrial switch of TGA or ccTGA have not been fully established. A durable VAD, including the HeartMate 3, was successfully implanted in four such patients in this study. Pre-operative three-dimensional computed tomography images and intraoperative transoesophageal echocardiography guidance helped to determine the positions of the inflow and pump.